Dealing with conflict - The role of the ward sister - L.M. Cremer (AOSIS, 1980)
In the course of her duties, the ward sister has to contend with many forms of conflict, discord and dissension. These involve conflict of the intrapersonal, interpersonal and intergroup varieties. Conflict is in the main, disruptive and dysfunctional. Skilful management, however, embodying cooperative effort in its reduction can produce constructive and positive results. Conflict management strategies are therefore either restrictive or constructive. Persons in serious conflict suffer varied degrees of personality disequilibrium, which necessitates emotional first aid or crisis intervention. Such primary preventive care is applicable to patients, their relatives, and members of the nursing staff in such need.